The Android Based Computer Network Monitoring Application - Muhammad Nashrullah; Muhammad Alif Raher (Politeknik Negeri Batam, 2018)
Utilization of information technology and computer network as data communication media has been increased. The requirement for shared use of existing resources in the network both software and hardware has resulted in the development of various technologies of the network itself. Information technology and communications are widely used today using computer network system as a medium of information and data transformation, the greater the company or agency that uses the network computer the more complex the network system in the company or agency, and required a good handling for the system can run optimally. One of them that uses computer network system is Banyan Tree Bintan. Network monitoring activities in Banyan Tree Bintan are important to do by network administrator to ensure the network is always in good condition. Given the limitations of network administrators who can not always be in the workplace, it is necessary for a system that can monitor the computer network remotely. So that the network administrator can know the state of the computer network at any time and can perform actions that need to be done quickly.This application is based on android using an Internet connection for network administrators can monitor network anytime and anywhere. Desktop-based applications need to be installed on the computer so that computer system data can be retrieved and displayed on android devices.